Pendampingan Penulisan Bahasa Arab pada Santri Mubtadi’ di Pesantren Berbasis Vokasi - Fina Aunul Kafi; Zainuri Zainuri (An-Nuqthah, 2026)
This community service aims to enhance Arabic writing skills (maharah kitabah) among five beginner santri at SMKN 2 Jember through participatory tutoring with an intensive mentoring approach based on practice and direct feedback over eight sessions. Employing a participatory design with pre-post tests, observation, and thematic analysis, results indicate an average score improvement from 42 to 82 (96% gain), particularly in hijaiyyah letter accuracy, harakat placement, and simple sentence structure. Findings are driven by reduced affective filter and repetitive drills addressing L1 interference. Implications suggest the model's effectiveness for non-formal learning in vocational pesantren, albeit limited by small sample size.